Effect of Financial Management Training Program on Micro, Small and Medium Enterprises (MSMEs) in Area Y - Susilawati, Made; Hermansyah, Eko Nur; Majid, Jamaluddin; Fatmasari, Ria Kristia; Ningrum, Dedah (Abdimas Indonesian Journal, 2024)
It can be argued that financial management training programs occupy an important position with respect to the enhancement of performance and sustainability in micro, small and medium-sized enterprises (MSMEs). This study aims to analyze the effect of financial management training programs on the financial management of MSMEs in Region Y. The research method employed is qualitative, utilizing in-depth interviews with 15 MSME owners who have attended the training. The findings indicate that the training facilitated an enhancement in MSMEs' comprehension of financial recording, budgeting, and cash flow management. Nevertheless, the implementation of the training was hindered by constraints in time and resources. This study presents recommendations for optimizing the training through a more practical and sustainable approach.